Using GIS for wildlife monitoring at the Alqueva Dam - Pereira, Miguel (2008)
Large dams affect enormously the local ecology (McCully 1998). The Alqueva dam, which has recently being built in Southern of Portugal, will flood an area of 25,000ha: habitat loss and fragmentation will displace many wildlife species, while others will be attracted by the new habitats. Given the complexity of biological data, the size of the affected area, and the need to analyse temporal data, GIS turned out to be the ideal working tool. At the UMC we have built a GIS that is being fed with data from 14 projects aimed at monitoring different biological groups (small mammals, otters, birds of prey, steppe birds, passerines, butterflies, dragonflies, beetles, fish) over an area of 176,000ha. The flooding of the area is expected for 2002, the species monitoring programme started in 1999.